The Overview of Nutritional Status and Blood Glucose Levels of Pregnant Women at the Ubud Health Center, Bali - Rinawati, Luh Putu; Sarihati, I Gusti Agung Dewi; Sundari, Cok Dewi Widhya Hana; Dhyanaputri, I Gusti Ayu Sri; Bekti, Heri Setiyo; Dwija, Ida Bagus Nyoman Putra (Poltekkes Kemenkes Palu, 2024)
The nutritional status of pregnant women can be determined by measuring the size of mid-upper arm circumference (MUAC) and body mass index (BMI). Women with excessive nutritional status have a high risk of various complications. This study aims to describe the nutritional status and blood glucose levels of pregnant women at the Ubud Health Center, Bali. This descriptive study was conducted on 27 pregnant women who had antenatal care at the Ubud Health Center. MUAC size was measured using a measuring tape, while BMI was measured by calculating body weight in kilograms divided by height in meters squared. Blood glucose levels were measured using the point of care testing (POCT) method. From 27 respondents, it was found that 23 respondents had normal MUAC, 3 respondents had less than normal, and 1 respondent was obese. Based on BMI, 14 respondents had normal BMI, 5 respondents were overweight, and 8 respondents were obese. For blood glucose levels, all respondents have normal levels. Respondents who have MUAC less than normal can be at risk of chronic energy deficiency, while respondents with the obese category can be at risk of GDM, hypertension, and cesarean section. Pregnant women with GDM can increase the risk of type 2 DM, cardiovascular disease and have the potential to give birth macrosomic babies. Pregnant women with GDM almost never give complaints, so screening is necessary. Screening can be done by measuring the nutritional status of pregnant women and blood glucose levels during antenatal care at health center.